Antiviral effect of Guazuma ulmifolia and Stryphnodendron adstringens on poliovirus and bovine herpesvirus - Felipe, AMM; Rincao, V. P.; Benati, F. J.; Linhares, REC; Galina, K. J.; de Toledo, CEM; Lopes, G. C.; de Mello, JCP; Nozawa, C. (Pharmaceutical Soc Japan, 2006)
Crude extract (CE) and aqueous (AqF) and ethyl acetate (EtOAcF) fractions of Guazuma ulmifolia LAM., Sterculiaceae and the corresponding AqF, EtOAcF of Stryphnodendron adstringens (MART.) COVILLE, Leguminosae were tested for their antiviral activity against poliovirus 1 (P-1) and bovine herpesvirus 1 (BHV-1) in HEp2 cultured cells. The antiviral activity was monitored by plaque assay and immunolluorescence assay (IFA) under virucidal and therapeutic protocols. The therapeutic protocol demonstrated statistically significant positive results with both plants and for both virus strains. The highest percentages of viral inhibition were found for G. ulmifolia EtOAcF which inhibited BHV-1 and P-1 replication by 100% and 99%, respectively (p < 0.05, Student's t-test). For S. adstringens, AqF was the most efficient, inhibiting BHV-1 and P-1 by 97% and 93%, respectively (p < 0.05). In the virucidal protocol, G. ulmifolia CE inhibited the replication of BHV-1 and P-1 by 60% and 26%, respectively (p < 0.05), while, for S. adstringens, inhibition of 62% (p < 0.05) was demonstrated only with EtOAcF for P-1. IFA demonstrated that the greatest reduction in fluorescent cell number occurred with G. ulmifolia, under the therapeutic protocol for both virus strains. However, AqF and EtOAcF of S. adstringens were most efficient with the virucidal protocol for P-1 In conclusion, we demonstrated that G. ulmifolia and S. adstringens inhibited BHV-1 and P-1 replication, as well as, blocked the synthesis of viral antigens in infected cell cultures.
Keywords: antiviral activity; plant extracts; poliovirus; bovine herpesvirus; cell culture